UJI FORMULASI BIOFUNGISIDA GRANULAR BERBAHAN AKTIF Trichoderma virens ENDOFIT DALAM MENGENDALIKAN Ganoderma Boninense Pat. PADA BIBIT KELAPA SAWIT (Elaeis guineensis Jacq.) - Adja Muhammad Alsan Shaf; Titania Tjandrawati Nugroho; Fifi Puspita (UIR Press, 2021)
The aim of this work is to find out the effect of granular bio fungicide formulations with the active ingredient of T. virens endophytes and to obtain the best biofungicide preparations to control G. boninense and improve the quality of oil palm seeds. The research was conducted at the experimental farm and plant disease laboratories, Faculty of Agriculture, the University of Riau from February 2017 to September 2018. The research was carried out experimentally using a completely randomized design (CRD). The treatment tested was the Trichoderma virens formulation F0 = Control without treatment, F0- = Control negative (Ganoderma inoculant), F0 + = Positive control (15 ml Trichoderma virens inoculant + Ganoderma inoculant), F1 = 15 ml Trichoderma virens inoculant +100 g sago starch + 25 peat peat +25 g tapioca starch, F2 = 15 ml Trichoderma virens inoculant +100 g palm frond flour + 25 sago dregs + 25 g tapioca flour, F3 = 15 ml Trichoderma virens inoculant + 100 g solid +25 g talc + 25 g flour tapioca, F4 = 15 ml Trichoderma virens inoculant + 100 g cocoa shell flour + 25 g zeolite + 25 g tapioca flour. The parameters observed were the intensity of the attack of the disease, seed height, weevil diameter, number of fronds, root volume, seed dry weight, and sprout ratio. uk root. The obtained data were statistically analyzed using variant fingerprints. The average results of the analysis were continued with the BNJ test at the 5% level. F4 treatment showed the best granular formulation for the growth and development of T. virens endophytes, inhibiting the infection of Ganoderma sp. Attack. on seedlings and better seed growth on observations of seed height, root volume, number of midribs, root crown ratio, and dry weight of oil palm seedlings.